28 Intraoperative Administration of Antifibrinolytic Drug Tranexamic Acid Is Not Associated with Decreased Intraoperative Blood Loss During Major Cardiac Surgery. (11th January 2018) - Compton, Frances; Wahed, Md Amer; Gregoric, Igor; Dasgupta, Amitava; Tint, Hlaing
Abstract: Antifibrinolytic drugs such as tranexamic acid are used to prevent blood loss in many clinical situations, including trauma patients and during cardiac surgery. The goal of this study is to examine the effectiveness of tranexamic acid in preventing intraoperative blood loss during major cardiac surgery. Out of an initial 81 patients undergoing major cardiac surgery (both coronary artery bypass and valve repair procedures) at our teaching hospital, 67 patients were selected for this study. Patients receiving significant intraoperative transfusion and or K-centra were excluded. In the first study, we selected patients who received no blood product and compared estimated blood loss, decrease in percent hemoglobin and hematocrit following surgery between two groups of patients, one group receiving no tranexamic acid (n = 17) and another group receiving tranexamic acid (n = 25). In the second study, we combined these patients with patients receiving modest amounts of blood products (1–2 units) and compared these parameters between two groups of patients (25 patients received no tranexamic acid, 42 patients received tranexamic acid). Statistical analyses were performed using independent t-test, two-tailed, and a difference was considered statistically significant at 95% confidence interval or higher ( P ≤ .05). In patients who received no blood products during surgery, those who received no tranexamic acid showed statistically significant reduced estimated blood loss (mean: 713.5 mL, SD: 351.6, n = 17) compared to those who received tranexamic acid (mean 987.2 mL, SD 459.9, n = 25). However, no statistically significant difference was observed in percent reduced hemoglobin concentration or percent reduced hematocrit associated with surgery between these two groups of patients. We observed similar results when patients receiving no blood products and patients receiving modest amount of blood products were combined based on use of tranexamic acid or not, as only estimated blood loss between these two groups was statistically significant (estimated blood loss in patients not receiving tranexamic acid: mean 814.0 mL, SD 501.6, n = 25; and estimated blood loss in patients receiving tranexamic acid: mean 1, 207.1 mL, SD 488.6, n = 42). We conclude that intraoperative antifibrinolytic therapy with tranexamic acid does not reduce intraoperative blood loss during major cardiac surgery, which contradicts popular belief.